Degradation of Methyl Violet Using TiO2-Bayah Natural Zeolite Photocatalyst - Kustiningsih, Indar; Restiani, Ria; Raharja, Teja; Hasna, Athia; Kartika Sari, Denni (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
Degradation of methyl violet using photocatalysis method has been investigated. In this study TiO2 was superimposed on the surface of the Bayah natural zeolite with two solvents, ethanol and distilled water. The activation of the Bayah natural zeolite using HCl. In this study the effect of zeolite size (60.80 and 100 mesh), the composition of TiO2-Zeolite (0.2, 0.4 and 0.6) and intensity of photon energy on the degradation of methyl violet has been evaluated. The samples were were characterized by means X-ray powder diffractometer (XRD). The specific surface area of each sample was determined by the BET nitrogen gas adsorption/desorption method. The measurement of methyl violet concentration using UV Vis spectrophotometry. The results showed the optimum composition of TiO2 in zeolite was 4 grams with a solvent of distilled water. By Using this sample could reduce methyl violet by 94,5% for 4 hours with UV light intensity of 1340 W /cm2.